The determinants of Facebook usage among SMEs in Malaysia / Nurfatihah Yusrey - Yusrey, Nurfatihah (Faculty of Business and Management, 2019)
The purpose of this study to identify the determinants of Facebook usage among SMEs in services sector in Malaysia. The information of SMEs were obtained from Majlis Amanah Rakyat (MARA). In this study, there are three independent variables which are interactivity, cost effectiveness, and compatibility. This research has adopted the descriptive research or known as correlational studies. The sampling design used in this study is non-probability sampling which is convenience sampling. Data from 84 respondents had been collected, thus researcher used Statistical Package for Social Science (SPSS) for data analysis. The analysis includes descriptive analysis, reliability analysis, and regression analysis. The finding from this study demonstrates that cost effectiveness and compatibility are accepted, while interactivity is rejected. In conclusion it shows that interactivity, cost effectiveness, and compatibility are related to Facebook usage among SMEs.